1998
DOI: 10.1007/s003300050393
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic embolization of a systemic arterialization of lung without sequestration

Abstract: We report the case of a 51-year-old man with massive haemoptysis due to a systemic arterialization of lung without sequestration. Unlike bronchopulmonary sequestration there was a normal bronchial distribution and the involved lung parenchyma was normal. Therefore a therapeutic transarterial embolization of the aberrant systemic vessel from the distal thoracic aorta was performed. The embolization was successful and the patient did not suffer from further haemoptysis during the subsequent follow-up of ten mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…Diagnosis is relatively easy with chest computed tomography (CT) (1,2). However, treatment options vary, including surgical resection of the involved lung and surgical ligation of the aberrant artery, and endovascular treatment has been recently introduced (3). We reported a case of a 24-year-old man with ASANL who was treated by the endovascular method.…”
Section: Introductionmentioning
confidence: 97%
“…Diagnosis is relatively easy with chest computed tomography (CT) (1,2). However, treatment options vary, including surgical resection of the involved lung and surgical ligation of the aberrant artery, and endovascular treatment has been recently introduced (3). We reported a case of a 24-year-old man with ASANL who was treated by the endovascular method.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3][4][5][6][7][8] The aberrant artery commonly arises from the descending thoracic aorta, as in our case, and sometimes from the proximal abdominal aorta or the celiac artery. [1][2][3]9,10 Pryce classified intralobar sequestration into three types according to the extent of the blood supply. An abnormal artery without bronchopulmonary sequestration is categorized as type 1; an abnormal artery supplying the sequestered plus adjacent normal lung is categorized as type 2; and an abnormal artery supplying only the sequestered lung is categorized as type 3.…”
Section: Discussionmentioning
confidence: 98%
“…3,9,10 Transarterial therapeutic coil embolization of such an artery was first reported by Bruhlmann et al in 1998 in a patient whose lung was supplied by both the aberrant artery and the pulmonary artery. 3 In 2002, Chabbert et al reported a similar patient with preserved pulmonary arterial flow in whom transient chest pain occurred within a few days after embolization. 10 Izzillo et al reported a case of true Pryce type l sequestration in 2000, in which the pulmonary artery was absent.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In some cases with massive hemorrhage transarterial embolization of the abnormal vessels is performed [10]. Contrast-enhanced MR angiography makes it easy to obtain the preoperative vascular map needed for this kind of surgery and TAE.…”
Section: Discussionmentioning
confidence: 99%